2021
DOI: 10.1016/j.jedc.2021.104099
|View full text |Cite
|
Sign up to set email alerts
|

Emissions trading with rolling horizons

Abstract: We build a model of competitive emissions trading under uncertainty with supply-side control. Firms can use rolling planning horizons to deal with uncertainty and can also exhibit bounded responsiveness to the control. We tailor the model to the EU ETS, calibrate it to 2008-2017 market developments and find that a rolling horizon is able to reconcile the banking dynamics with discount rates implied from futures' yield curves. We evaluate the 2018 market reform, decompose the impacts of its main features and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 121 publications
(150 reference statements)
1
22
0
Order By: Relevance
“…Although such assumptions do not reflect reality, they allow for a first-best analysis, unaffected by imperfections of real-life decision makers. Myopic decision making 26 may lead to shorter waterbed punctures and lower invalidation volumes. Risk-aversion 27 , on the other hand, may prolong the duration of the waterbed puncture and increase invalidation volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such assumptions do not reflect reality, they allow for a first-best analysis, unaffected by imperfections of real-life decision makers. Myopic decision making 26 may lead to shorter waterbed punctures and lower invalidation volumes. Risk-aversion 27 , on the other hand, may prolong the duration of the waterbed puncture and increase invalidation volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the invalidation rule thus implies a counter-intuitive, self-reinforcing relation between the future cost of abatement and the invalidation volume, making the invalidation rule more stringent when the cost of compliance is higher—an effect first discussed by Bruninx et al 19 .This surprising result crucially depends on the assumption that market participants are intertemporally optimizing over the full horizon of the EU ETS. Indeed, in models with a limited horizon 26 market participants do not consider the challenges further in the future and will abate less, which decreases cumulative invalidation. As a result, the positive correlation between the convexity of the marginal abatement cost curve and invalidation increases the more market participants look further into the future, assuming they face the same marginal abatement cost curve.…”
Section: Methodsmentioning
confidence: 99%
“…Several other papers consider risk aversion(Baldursson and von der Fehr 2004;Colla et al 2012;Haita-Falah 2016) and ambiguity aversion(Quemin 2017) in permit markets. However, all of them have a different focus than we do.7 Beck and Kruse-Andersen (2018),Bocklet et al 2019, Bruninx et al (2018,Carlén et al (2019), Gerlagh et al 2019, Quemin and Trotignon (2019 andPerino and Willner (2017).…”
mentioning
confidence: 84%
“…However, these papers assume given discount rates and ignore uncertainty. An exception is provided by Quemin and Trotignon (2019) who analyze the impact of firms' limited planning horizons and limited responsiveness to the MSR. They find a relatively high number of permanent permit withdrawals (5 to 10 Gt) compared to the literature (1.7 to 6.0 Gt) especially if the firms have a limited horizon.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the emission reduction effect of ETSs, the existing studies mostly carry out empirical analysis based on samples from Europe and China, and most of the studies confirm the effectiveness of these systems (Quemin & Trotignon, 2021). For example, Krishnamurti and Hoque (2011) studied the efficiency of the European emission option market and found that option pricing in the European emission trading market is efficient, with short-term option pricing being particularly efficient.…”
Section: Introductionmentioning
confidence: 99%